ANALYSIS OF SCIENTIFIC HABITS OF MIND ENERGY ISSUES INVENTORY (SHOMEII) INSTRUMENT: RASCH MODEL - Mulvia, Rahmadhani; Ramalis, Taufik Ramlan; Efendi, Ridwan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
ANALYSIS OF SCIENTIFIC HABITS OF MIND ENERGY ISSUES INVENTORY (SHOMEII) INSTRUMENT: RASCH MODELAbstractScientific Habits of Mind (SHOM) is a thinking characteristic that individuals have in solving problems and making decisions. SHOM can be accomplished in learning such as physics education through discussion, debate, and issue-based learning. However, the instrument for measuring SHOM in physics education is still immature. The purpose of this research is to develop and identify the quality of the SHOM instrument with energy problems analyzed using Model Rasch. This instrument is known as the Scientific Habits of Mind Energy Issue Inventory (SHOMEII). The development was carried out with the 3D+1I model (defining, designing, developing and implementing), involving 280 high school students with an average age of 17 years and came from West Java, Indonesia. The instruments used were a validation sheet and a SHOMEII consisting of 22 items with 4 answer choices based on the level of confidence. The results of the analysis show that SHOMEII has excellent reliability, good validity, and varying levels of difficulty. Therefore, SHOMEII can be implication as an instrument to measure students' SHOM abilities in physics education.AbstrakScientific Habits of Mind (SHOM) merupakan karakteristik berpikir seperti ilmuwan dalam melakukan sesuatu, memecahkan masalah dan mengambil keputusan. SHOM dapat dilatihkan dengan diskusi, debat dan pembelajaran berbasis isu. Akan tetapi, instrumen untuk mengukur SHOM dalam pendidikan fisika kurang berkembang. Tujuan penelitian ini adalah untuk mengembangkan dan mengidentifikasi kualitas instrumen SHOM dengan isu energi yang dianalisis Model Rasch, dikenal dengan Scientific Habits of Mind Energy Issues Inventory (SHOMEII). Metode penelitian ini adalah pengembangan dengan model 3D+1I (defining, designing, developing dan implementing) yang melibatkan 280 peserta didik SMA berasal dari Jawa Barat, Indonesia. Instrumen yang digunakan adalah lembar validasi dan SHOMEII terdiri dari 22 item dengan 4 pilihan jawaban berdasarkan tingkat kepercayaan. Hasil analisis, SHOMEII memiliki reliabilitas yang sangat baik, validitas yang baik dan tingkat kesukaran yang beragam. Oleh karena itu, SHOMEII dapat diimplikasikan sebagai instrumen untuk kemampuan SHOM peserta didik pada pendidikan fisika.Â